Is Malaysia’s banded langur, Presbytis femoralis femoralis, actually Presbytis neglectus neglectus? Taxonomic revision with new insights on the radiation history of the Presbytis species group in Southeast Asia - Abu Bakar, Muhammad Abdul‑Latiff; Baharuddin, Hanisah; Abdul‑Patah, Pazil; Md‑Zain, Badrul Munir (Springer, 2018)
The disjunct distribution of Presbytis femoralis subspecies across Sumatra (P. f. percura), southern (P. f. femoralis) and northern (P. f. robinsoni) Peninsular Malaysia marks the unique vicariance events in the Sunda Shelf. However, the taxonomic positions and evolutionary history of P. f. femoralis are unresolved after decades of research. To elucidate this evolutionary history, we analyzed 501 base pairs of the mitochondrial HVSI gene from 25 individuals representing Malaysia’s banded langur, with the addition of 29 sequences of Asian Presbytis from Genbank. Our results revealed closer affinity of P. f. femoralis to P. m. mitrata and P. m. sumatrana while maintaining the monophyletic state of P. f. femoralis as compared to P. f. robinsoni. Two central theses were inferred from the results; (1) P. f. femoralis does not belong in the same species classification as P. f. robinsoni, and (2) P. f. femoralis is the basal lineage of the Presbytis in Peninsular Malaysia. Proving the first hypothesis through genetic analysis, we reassigned P. f. femoralis of Malaysia to Presbytis neglectus (Schlegel’s banded langur) (Schlegel in Revue Methodique, Museum d’Histoire Naturelle des Pays-Bas 7:1, 1876) following the International Code of Zoological Nomenclature (article 23.3). The ancestors of P. neglectus are hypothesized to have reached southern Peninsular Malaysia during the Pleistocene and survived in refugium along the western coast. Consequently, they radiated upward, forming P. f. robinsoni and P. siamensis resulting in the highly allopatric distribution in Peninsular Malaysia. This study has successfully resolved the taxonomic position of P. neglectus in Peninsular Malaysia while providing an alternative biogeographic theory for the Asian Presbytis.